You Belong With Us? A Netnographic Study of Status and Hierarchy in the Taylor Swift Fan Community - Feng,Sandra; Ramos Otiniano,Arianna (2026)
This study explored how fans gain and maintain status through consumption practices in online pop music fan communities, focusing on the role of consumption, peer evaluation, platform visibility, and artist participation. Drawing on Bourdieu’s concepts of capital and symbolic violence, Thornton’s subcultural capital theory, and Lamont’s symbolic boundaries, the study examined how status is constructed and negotiated within online fandom spaces. A qualitative netnographic approach was adopted, using purposive and intensive sampling of Taylor Swift-related subreddits. Data were analyzed through a six-phase thematic analysis informed by a relativist ontology, social constructionist epistemology, and abductive research approach. The findings revealed that status within the online Swiftie community was constructed through three interconnected dimensions: demonstrating dedication through visible consumption practices such as collecting, streaming, fan labor, and expertise; policing and judgment through distinctions between “real” and “casual” fans and moral evaluations of artists and fandom; and perceived proximity to Taylor Swift, shaped by platform metrics and marketing strategies. The study concludes that status in online fan communities is not fixed but continuously negotiated through practices that gain value when made visible and validated by other fans. The findings contribute to research on brand communities, parasocial relationships, and subcultural capital by highlighting the active role of artists in shaping status hierarchies and the tensions between fan devotion and commercial systems.
Keywords: Status; Fandom; Taylor Swift; Consumption; Netnography; Hierarchies